Transit of the Interplanetary Shocks Associated with Type II Radio Bursts Within 1AU - Su Yeon Oh; Yu Yi; Yong Ha Kim (Journal of Astronomy and Space Sciences, 2007)
Among the interplanetary shock (IP shock)s observed by ACE spacecraft at 1AU during 1997 to 2000, we have selected 31 IP shocks which had triggered the interplanetary type II radio bursts detected by the WIND spacecraft while those shocks were leaving the Sun. We compared the observed IP shock propagation speeds and the IP shock transit speeds estimated by time difference between the interplanetary type II radio burst detection and the IP shock observation. Then, we found that the mean acceleration of the IP shocks between the Sun and the Earth is about -1.02 m/sec^2, which means the deceleration contrary to the positive acceleration predicted by Parker solar wind model. It is also verified that the acceleration of the IP shock does not show any linear correlation with the shock propagation speed and the Mach number of the IP shock.